Effect of waves on the tidal energy resource at a planned tidal stream array. (March 2015) - Hashemi, M. Reza; Neill, Simon P.; Robins, Peter E.; Davies, Alan G.; Lewis, Matt J.
Abstract: Wave–current interaction (WCI) processes can potentially alter tidal currents, and consequently affect the tidal stream resource at wave exposed sites. In this research, a high resolution coupled wave-tide model of a proposed tidal stream array has been developed. We investigated the effect of WCI processes on the tidal resource of the site for typical dominant wave scenarios of the region. We have implemented a simplified method to include the effect of waves on bottom friction. The results show that as a consequence of the combined effects of the wave radiation stresses and enhanced bottom friction, the tidal energy resource can be reduced by up to 20% and 15%, for extreme and mean winter wave scenarios, respectively. Whilst this study assessed the impact for a site relatively exposed to waves, the magnitude of this effect is variable depending on the wave climate of a region, and is expected to be different, particularly, in sites which are more exposed to waves. Such effects can be investigated in detail in future studies using a similar procedure to that presented here. It was also shown that the wind generated currents due to wind shear stress can alter the distribution of this effect. Highlights: We simulate the effect of waves on the tidal energy resource at a tidal stream site. Enhanced bottom friction and wave radiation stresses can significantly affect tidal energy. The effect on tidal power can reach 20% for extreme wave conditions. The effect on tidal power can reach 15% for mean winter wave conditions. More impact is expected at sites which are more exposed to waves.